Christianity, art and transformation : - Gruchy, John W. De (Cambridge University Press, 2001)
Christianity, Art and Transformation is a journey of exploration that is both historical and contemporary, theological and practical. The reader is invited to share in the journey beginning in the life of the early church, travelling through the history of European Christianity and art, and arriving in southern Africa. Many themes weave through its pages, among them the nature of beauty, good taste, the power of sacred images, aesthetics and ethics, and the role of art in society and the church today.